Municipalities' development to ensure environmentally sustainable procurement - Karlsson, Viktor; Wallin, Jonathan (My University, 2022)
Sustainable construction has become an important part of the construction industry, and clear and anchored environmental requirements in public procurement are required to ensure that the construction that takes place is sustainable. There is currently a disparity in how different municipalities choose to prioritize their sustainability requirements in public procurement. There are national roadmaps where researchers and industry leaders address challenges and propose improvement measures to deal with the transition to a sustainable construction industry. The goal of this thesis is to investigate the challenges and barriers that municipalities face today. Because procurement is viewed as a powerful tool for implementing sustainable work, the thesis must identify problem areas to ensure sustainable public procurement. The report is primarily based on empirical data, roadmaps, and national documents, but it is also grounded in relevant field theory. Governance, resources, and cooperation have emerged as the most significant impediments. We learned about how different municipalities operate through our research and discovered a disparity in how municipalities choose to set requirements for public procurement. When the environment is confronted with economic and organizational issues, a complex problem arises that cannot be handled by a single municipality; therefore, a collaborative effort is required to cope with the necessary sustainable adjustment for the construction industry.
Keywords: Sustainable procurement, governance, collaboration, resources; procurement requirements, partnering